2021
DOI: 10.2147/ott.s325443
|View full text |Cite
|
Sign up to set email alerts
|

High Tumor Mutation Burden and DNA Repair Gene Mutations are Associated with Primary Resistance to Crizotinib in ALK-Rearranged Lung Cancer

Abstract: Background About 20% of patients with ALK -rearranged non-small cell lung cancer (NSCLC) develop acquired resistance to tyrosine kinase inhibitor (TKI) during the first 6 months. This study aimed to examine the molecular mechanisms of early TKI resistance and prognosis in ALK -rearranged NSCLC. Methods Ten patients with ALK -rearranged NSCLC were included: five who developed rapid resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The gene mutation landscape showed that the most common co-mutation genes of ALK positive patients in our study were TP53 and KMT2C, which were reported functions in cell proliferation, tumor formation and DNA damage repair ( 30 - 34 ). At baseline, patients with TP53 mutation had higher gene mutation load, which was reported associated with primary resistance to crizotinib in ALK+ NSCLC ( 35 ). We found that patients with low ALK mutation abundance at baseline achieved significantly longer mPFS compared to those with high ALK mutation abundance.…”
Section: Discussionmentioning
confidence: 92%
“…The gene mutation landscape showed that the most common co-mutation genes of ALK positive patients in our study were TP53 and KMT2C, which were reported functions in cell proliferation, tumor formation and DNA damage repair ( 30 - 34 ). At baseline, patients with TP53 mutation had higher gene mutation load, which was reported associated with primary resistance to crizotinib in ALK+ NSCLC ( 35 ). We found that patients with low ALK mutation abundance at baseline achieved significantly longer mPFS compared to those with high ALK mutation abundance.…”
Section: Discussionmentioning
confidence: 92%
“…Since there are few studies on primary resistance to ALK TKIs, the potential mechanism of drug resistance is not yet clear. Several case reports revealed possible intrinsic factors of primary resistance to crizotinib, including MYC amplification [ 195 ], ALK/KRAS co-alteration [ 196 , 197 ], Bim deletion polymorphism [ 198 ], high tumor mutational burden (TMB), and mutations in DNA repair genes (including TP53 G245S) [ 199 ]. More efforts should be made to explore the mechanisms of primary resistance to improve the treatment efficiency of these patients.…”
Section: Alk Gene Rearrangementsmentioning
confidence: 99%